2020
DOI: 10.1136/bmjopen-2019-031592
|View full text |Cite
|
Sign up to set email alerts
|

Central Sensitisation and functioning in patients with chronic low back pain: protocol for a cross-sectional and cohort study

Abstract: IntroductionA relevant subsample of patients with chronic low back pain (CLBP) have manifested augmented central pain processing, central sensitisation (CS). Patients with CLBP have limited functioning and participation. Theoretically, physical functioning in patients with CLBP can plausibly be linked to CS; however, evidence to explain such association is scarce. Moreover, there is no gold standard for CS diagnosis. The objectives of the study are: (1) to analyse the association between instruments assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 99 publications
0
13
0
Order By: Relevance
“…The measurement of the ANS response to noxious stimulation in patients with CS is seen as a viable promise for finding an objective parameter that would confirm NP. 17 A recent study by Nickel et al, 18 showed that sympathetic function is more related to stimulus intensity than perceived pain intensity. A similar observation was provided in our previous studies on a minimally invasive procedure applied to patients with both LBLP and MPS.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of the ANS response to noxious stimulation in patients with CS is seen as a viable promise for finding an objective parameter that would confirm NP. 17 A recent study by Nickel et al, 18 showed that sympathetic function is more related to stimulus intensity than perceived pain intensity. A similar observation was provided in our previous studies on a minimally invasive procedure applied to patients with both LBLP and MPS.…”
Section: Introductionmentioning
confidence: 99%
“…In NSLBP, pain sensations do not necessarily reflect the presence of a peripheral noxious stimulus because neurons in the pain pathway can be activated by a low threshold, innocuous or non-noxious inputs [13]. The neurobiological cause is thought to be maladaptive plasticity such as central sensitization, which manifests as distort or amplify (hyperalgesia and allodynia), increase degree or duration (after sensations and temporal summation), and spatial extent (expansion of the receptive field), as well as a reduced conditioned pain modulation [13,14]. In chronic pain patients, the prevalent expectation for brain activity is a sustained or enhanced activation of areas already identified for acute pain [15].…”
Section: Introductionmentioning
confidence: 99%
“…However, some data indicate its diagnostic utility in cases when noxious stimulation is involved, and immediate ANS imbalance reactions are registered [18][19][20]. Heart rate variability (HRV) has been proposed to support the central sensitization examination [21,22]. It has remarkable potential, especially for nociplastic pain, where ANS dysregulation is an important factor.…”
Section: Autonomic Nervous System-a Possible Marker Of Nociplastic Pain Involvementmentioning
confidence: 99%